Six new species and 1 new species record of Orthotrichia (Trichoptera: Hydroptilidae) from China - Lei, Zhou; Lian-Fang, Yang; Morse, John C. (Zootaxa, 2010)
Six new species of the caddisfly genus Orthotrichia are described and illustrated from China, namely Or. apophysis Zhou & Yang, sp. nov.; Or. latiramifera Zhou & Yang, sp. nov.; Or. cornuta Zhou &Yang, sp. nov.; Or. discedata Zhou & Morse, sp. nov.; Or. cuspidigera Zhou & Yang, sp. nov.; and Or. subrhomba Zhou & Morse, sp. nov.. One species, Or. terpsichore Malicky & Chantaramongkol, 2007, is recorded for the first time from China, bringing the number of species of the genus known from China to 14. Of these, 10 species are distributed among 3 species groups of Marshall (1979), with 4 species unassigned. The known distributions for all the Chinese Orthotrichia species are provided.